2009
DOI: 10.4049/jimmunol.182.2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Lymphocytic Choriomeningitis Virus-Induced Inflammation of the CNS Involves a Cytokine-Chemokine-Cytokine-Chemokine Cascade

Abstract: Intracerebral inoculation of immunocompetent mice with lymphocytic choriomeningitis virus (LCMV) normally results in fatal CD8+ T cell mediated meningoencephalitis. However, in CXCL10-deficient mice, the virus-induced CD8+ T cell accumulation in the neural parenchyma is impaired, and only 30–50% of the mice succumb to the infection. Similar results are obtained in mice deficient in the matching chemokine receptor, CXCR3. Together, these findings point to a key role for CXCL10 in regulating the severity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…The expression levels of these two ISGs were used as surrogate markers for the induction of type I IFN, because we had previously observed that the level of expression of type I IFNs in the LCMV-infected CNS borders on the level of detection (8); this approach is validated by our observation that there is no virus-induced increase in the expression of either of these genes in LCMV-infected IFNAR Ϫ/Ϫ mice (8).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The expression levels of these two ISGs were used as surrogate markers for the induction of type I IFN, because we had previously observed that the level of expression of type I IFNs in the LCMV-infected CNS borders on the level of detection (8); this approach is validated by our observation that there is no virus-induced increase in the expression of either of these genes in LCMV-infected IFNAR Ϫ/Ϫ mice (8).…”
Section: Resultsmentioning
confidence: 77%
“…A key factor in this recruitment seems to be the local production of the chemokine CXCL10, which interacts with the chemokine receptor CXCR3 on the activated CD8 T cells (6,7). Upon contact between incoming CD8 T cells and virus-infected cells in different parts of the CNS, large amounts of type II IFN are released, further increasing the local production of important chemoattractants, including CXCL10 (8). The whole process culminates in a severe CD8 ϩ T-cell-mediated inflammatory reaction in essential parts of the CNS, cerebral edema, and death 7 to 9 days after virus inoculation (8,35).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CXCL10 has been reported to play an important role in host defense following a variety of viral infections. Using CXCL10 2/2 mice, the major function for CXCL10 in host defense against viral infection has been shown to be recruitment of effector T cells and NK cells to sites of infection/inflammation (19)(20)(21)(22)(23)(24)(25). However, CXCL10 function specific to DENV infection has not been examined in vivo.…”
Section: Engue Virus (Denv)mentioning
confidence: 99%